ANALISA PENGGUNAAN CONTENT VIDEO DAN LIVE STREAMING TIKTOK DALAM MEMPENGARUHI MINAT BELI GEN Z - Siti Saadah; Zakiyya Tunnufus; Maesaroh; Mukti, Muhi (Universitas La Tansa Mashiro, 2025)
The number of people interested in the TikTok application is increasing, and the majority of its users are Generation Z. This can be utilized by business owners to market their products. Thus, business owners must be more creative in increasing Gen Z's purchasing interest so that they are interested in the video and live streaming content used. This study aims to analyze the use of TikTok video and livestreaming content in influencing Gen Z's purchasing interest. The data used in this research is primary data obtained from the results of distributing questionnaires to 50 respondents. This study used a quantitative method with a purposive sampling technique. Data analysis used multiple linear regression analysis assisted by SPSS Software Version 20. In this study, several problems were found related to service quality and price, both of which have the potential to increase customer satisfaction. The results partially video content variable has no effect on purchase intention variable. The live streaming variable partially influences buying interest. Simultaneously having video content and live streaming results together influences buying interest of gen Z.